Performance test of the cryogenic cooling system for the superconducting fault current limiter. Issue 1 (November 2015) - Hong, Yong-Ju; In, Sehwan; Yeom, Han-Kil; Kim, Heesun; Kim, Hye-Rim
Abstract: A Superconducting Fault Current Limiter is an electric power device which limits the fault current immediately in a power grid. The SFCL must be cooled to below the critical temperature of high temperature superconductor modules. In general, they are submerged in sub-cooled liquid nitrogen for their stable thermal characteristics. To cool and maintain the target temperature and pressure of the sub-cooled liquid nitrogen, the cryogenic cooling system should be designed well with a cryocooler and coolant circulation devices. The pressure of the cryostat for the SFCL should be pressurized to suppress the generation of nitrogen bubbles in quench mode of the SFCL. In this study, we tested the performance of the cooling system for the prototype 154 kV SFCL, which consist of a Stirling cryocooler, a subcooling cryostat, a pressure builder and a main cryostat for the SFCL module, to verify the design of the cooling system and the electric performance of the SFCL. The normal operation condition of the main cryostat is 71 K and 500 kPa. This paper presents tests results of the overall cooling system.